Study on the English-Chinese Translation of Business Contracts from the Perspective of Skopos Theory - Tang, Dongxu (Journal of Theory and Practice in Linguistics, 2024)
Business contracts play a crucial role in facilitating trade cooperation by clearly stipulating the responsibilities, rights, and other relevant matters of the involved parties. Accurate and concise translation of business contracts is therefore essential for ensuring smooth and effective trade cooperation. While many scholars have explored the principles and application of translation theories such as Functional Equivalence and Stylistics in the context of business contract translation, Skopos Theory offers a unique perspective that can provide valuable insights into the purpose-driven nature of translation. Skopos Theory emphasizes the importance of aligning translation strategies with specific aims, intra-textual coherence, and inter-textual coherence. This study will first introduce the historical development of Skopos Theory, then analyze the linguistic features of business contracts, and finally propose translation approaches based on the application of Skopos Theory.